Lucky loser : adventures in tennis & comedy - Kosta, Michael (Harper Influence, 2025)
"Before Michael Kosta was performing stand-up comedy specials and hosting The Daily Show, he was a professional tennis 'star,' reaching the lofty heights of the #864 ranked men's singles player in the world. Stop laughing. That's better than your world ranking. As a tennis pro, Kosta traveled across the globe, competing in such exotic locales as the Netherlands, Tokyo, and even rural Illinois before deciding to put down his racket and pursue a more stable and predictable career: comedy. In a completely unexpected and wild journey through the backwaters of professional tennis, Kosta shows the unlikely ways life on the court prepared him for life in front of a microphone. Like comedy, tennis is brutally competitive, and most people lose at it. Unlike comedy, no one in tennis puts a gun on the table as they count out your earnings in twenty-dollar bills at the end of the night. And then there are the things that have more to do with what happens to you--and what you end up learning--as part of growing up. Topics include: how to properly discard an unwanted European hard-boiled egg, giving CPR to your dead grandpa, cringe-worthy 'sex' in the Red Light District, crying so hard in a car that strangers call the cops, and also happy things like what it feels like when your dreams come true"--Provided by publisher.